2015
DOI: 10.1002/2014ja020764
|View full text |Cite
|
Sign up to set email alerts
|

Subpacket structures in EMIC rising tone emissions observed by the THEMIS probes

Abstract: We report subpacket structures found in electromagnetic ion cyclotron (EMIC) rising tone emissions observed by the Time History of Events and Macroscale Interactions during Substorms (THEMIS) probes. We investigate three typical cases in detail. The first case shows a continuous single rising tone with four obvious subpackets, and the second case is characterized by a patchy emission with multiple subpackets triggered in a broadband frequency. The third case looks like a smooth rising tone without any obvious … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
51
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 33 publications
4
51
0
Order By: Relevance
“…Nakamura et al [2015] showed using Time History of Events and Macroscale Interactions during Substorms (fleet of five satellites) satellite observations that the subpacket structures of EMIC-triggered emissions are in good agreement with the nonlinear transition time, supporting the model of Shoji and Omura [2013]. Thus, the time span of each subpacket structure of the EMIC-triggered emissions is also characterized by a nonlinear transition time, which is inversely proportional to the square root of the wave amplitude.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Nakamura et al [2015] showed using Time History of Events and Macroscale Interactions during Substorms (fleet of five satellites) satellite observations that the subpacket structures of EMIC-triggered emissions are in good agreement with the nonlinear transition time, supporting the model of Shoji and Omura [2013]. Thus, the time span of each subpacket structure of the EMIC-triggered emissions is also characterized by a nonlinear transition time, which is inversely proportional to the square root of the wave amplitude.…”
Section: Discussionmentioning
confidence: 56%
“…A portion of the scattered energetic ions falls into the upper atmospheric loss cone, and the ion precipitation can then be observed as a proton aurora [Frey et al, 2004;Yahnin et al, 2007]. They did not report many faster luminosity modulations of PPA that may be related to the subpacket structures of Pc1/EMIC waves observed with amplitude modulations [Usanova et al, 2010;Nakamura et al, 2015]. Isolated proton aurora can be displayed as an ionospheric projection of the location, duration, and evolution of the wave-particle interaction region in the magnetosphere .…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that the change of instantaneous frequencies may include pseudo rising-or falling-tones due to frequency jumps from emission to another emission. of EMIC rising tones (and whistler-mode chorus as well), which are called "subpacket structure" (Nakamura et al, 2015;Shoji & Omura, 2013). We can read that several short rising tones around 07:06 UT have an order of~0.1 Hz/s of frequency sweep rate.…”
Section: Intense Emic Emissions During Magnetospheric Compressionmentioning
confidence: 99%
“…Pickett et al [], Grison et al [], and Nakamura et al [, ] found rising tone emissions which have left‐handed circular polarization and frequency‐time dispersion of ∼30 s/Hz, using Cluster and Time History of Events and Macroscale Interactions during Substorms (THEMIS) satellite observations. Some of these rising tone emissions were in the helium band which is between the local oxygen and helium cyclotron frequencies and are in the Pc1 wave range of 0.2–5.0 Hz [ Jacobs et al , ].…”
Section: Introductionmentioning
confidence: 99%